CORRELATION ANALYSIS OF KOMODO NATIONAL PARK TOURISM ON ECONOMIC GROWTH OF WEST MANGGARAI REGENCY EAST NUSA TENGGARA PROVINCE - DIAN NURILMA (NIM: 21316303), AHMADA
With the increasing number of tourism visitors at Komodo National Park, the economic growth of West Manggarai Regency has increased mainly from sectors related to tourism activities. In Indonesia, the tourism sector ranked fourth largest contributor of foreign exchange after the oil and gas, coal, and palm oil. The objectives of this research are to calculate the multiplier effect of economic activity caused by tourism of Komodo National Park, calculate income disparity among the tourism business actors in West Manggarai, estimate the economics value of Varanus komodoensis, and analyze the correlation between economic growth of West Manggarai and the economic value of Varanus komodoensis. This research uses Keynesian Multiplier Effect to measure the economic impact that happened in West Manggarai Regency caused by the tourism of Komodo National Park. The income disparity between business actors is measured by Gini Coefficient and Lorenz Curve. Estimation of Varanus komodoensis value is obtained by using individual Travel Cost Method and the correlation between economic growth of West Manggarai and economic value of Varanus komodoensis is measured by Pearson method. The results showed that the value of keynesian multiplier effect of Komodo National Park tourism is more than one (>1) or Komodo National Park tourism has been able to provide economic impact for people in West Manggarai regency. Gini coefficient between tourism business actors in West Manggarai regency is 0.503 which means that income inequality is high. The economic value of komodo dragon is Rp 5.995.232.147.515,00 in 2017 and the value of each individual komodo dragon is Rp 2.110.254.188,00 per individual in 2017. Pearson's correlation shows that there is no significant relationship between economic growth and the economic value of komodo dragons. Nevertheless, the tourism activity of Komodo National Park has a significant impact on the economic growth of West Manggarai Regency.